2015
DOI: 10.3389/fpsyg.2015.01122
|View full text |Cite
|
Sign up to set email alerts
|

Facial mimicry in its social setting

Abstract: In interpersonal encounters, individuals often exhibit changes in their own facial expressions in response to emotional expressions of another person. Such changes are often called facial mimicry. While this tendency first appeared to be an automatic tendency of the perceiver to show the same emotional expression as the sender, evidence is now accumulating that situation, person, and relationship jointly determine whether and for which emotions such congruent facial behavior is shown. We review the evidence re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
143
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(152 citation statements)
references
References 157 publications
(206 reference statements)
9
143
0
Order By: Relevance
“…An increasing number of the studies have argued that FM may be dependent on many particular factors (for review see Hess and Fischer, 2013; Seibt et al, 2015), including the type of task the participant is engaged in Korb et al (2010) and Murata et al (2016), properties of the stimulus (dynamic vs. static presentation) (Weyers et al, 2006; Sato et al, 2008; Rymarczyk et al, 2011, 2016) and personal characteristics of the perceiver (e.g., empathic traits) (Sonnby-Borgström et al, 2003; Dimberg et al, 2011; Balconi and Canavesio, 2016). Recently, it has been shown that hormonal level, i.e., administration of oxytocin (Korb et al, 2016) as well as cultural norms (Wood et al, 2016) influence FM expression.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An increasing number of the studies have argued that FM may be dependent on many particular factors (for review see Hess and Fischer, 2013; Seibt et al, 2015), including the type of task the participant is engaged in Korb et al (2010) and Murata et al (2016), properties of the stimulus (dynamic vs. static presentation) (Weyers et al, 2006; Sato et al, 2008; Rymarczyk et al, 2011, 2016) and personal characteristics of the perceiver (e.g., empathic traits) (Sonnby-Borgström et al, 2003; Dimberg et al, 2011; Balconi and Canavesio, 2016). Recently, it has been shown that hormonal level, i.e., administration of oxytocin (Korb et al, 2016) as well as cultural norms (Wood et al, 2016) influence FM expression.…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable evidence that dynamic information is beneficial for various aspects of face processing, e.g., emotion recognition or judgments of intensity and arousal (for review see Krumhuber et al, 2013). Moreover, some studies have reported stronger emotion-specific responses to dynamic as opposed to static expressions, mainly the zygomaticus major muscle (ZM) (Weyers et al, 2006; Rymarczyk et al, 2011) and the corrugator supercilii muscle (CS) for happiness and anger (Sato et al, 2008), respectively; however, the available data is not consistent (for review see Seibt et al, 2015). This may be associated with the different methodologies that were used, e.g., different kinds of stimuli used across studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several research studies have shown that emotions and facial emotional expressions play an important role in everyday life [7,11,12]. Indeed, there is a wide field of research dealing with questions concerning emotional facial expressions as a signal that mediates social interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Research investigating interpersonal interaction of emotional facial expressions, mostly using electromyography (EMG), has demonstrated such communication to be rapid, automatic, and largely unconscious [9, 10]. Overall, observing emotional facial expressions in others elicits motor activation involved in the production of the expression observed [10].…”
Section: Introductionmentioning
confidence: 99%